2022
DOI: 10.21931/rb/2022.07.04.69
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lipid profile with HbA1c in type 2 diabetic Iraqi patients

Abstract: Insulin-induced hyperglycemia is the hallmark of diabetes mellitus (DM), including various metabolic disorders. Diabetic people are more likely to develop dyslipidemia, hypertension, and obesity. Type 2 diabetes ‎(T2DM), the most common illness, is generally asymptomatic in its early stages and can go misdiagnosed for years. Diabetes screening may be beneficial in some cases since early identification and treatment can lessen the burden of diabetes and its consequences.‎ This study aimed to find the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Diabetic individuals often have high LDL and triacylglycerol values and low HDL. The current investigation results revealed that individuals with diabetes had a higher lipid profile (5).…”
Section: Resultssupporting
confidence: 47%
“…Diabetic individuals often have high LDL and triacylglycerol values and low HDL. The current investigation results revealed that individuals with diabetes had a higher lipid profile (5).…”
Section: Resultssupporting
confidence: 47%